Functional identity of typhoon-derived green litter overrides functional dissimilarity in reshaping litter faunal feeding guilds in a subtropical forest - Shuning Ma; Lifeng Wang; Qingjun Ma; Ajuan Zhang; Rui Cao; Zhuang Wang; Qin Wang; Mei Qin; Wanqin Yang (Plant and Soil, 2026)

Heavy metals migration and in-situ solidification in the co-combustion of solid waste fuels: Rules and differences - Shuning Qin; Li Jia; Xiaolei Qiao; Chenxing Wang; Baihe Guo; Xinyue Chang; Peng Cheng; Yan Jin (Journal of Environmental Chemical Engineering, 2025)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Study on regeneration mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Yan Jin; Shuning Qin (Science of The Total Environment, 2024)

Modeling abrupt changes in mine water inflow trends: A CEEMDAN-based multi-model prediction approach - Dongze Yao; Shi Chen; Shuning Dong; Jiwei Qin (Journal of Cleaner Production, 2024)

Study on the decarbonization mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Shuning Qin; Ling He; Yawen Wu; Qingrui Liu; Yan Jin (Fuel, 2024)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.